Analisis Pengaruh Pengetahuan dan Religiusitas Terhadap Niat Pembelian Produk Kosmetik Halal - Maharani, Novita Kusuma; Silvia, Ani (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2019)
The development of the halal economy comes from global Muslim consumers who indeed live a halal lifestyle. A halal lifestyle that includes the food they eat, about pharmacy and medicine, body care, cosmetics, banking services, travel, education, entertainment, and so on. In fact, the value of halal globally is estimated at US $ 2.1 trillion per year. The issue of halal cosmetics began to develop precisely after the rapid progress of the food and financial industry in accordance with Islamic principles. The development of halal cosmetics is so rapid at this time a product that is very steal the attention of women. This study aims to examine the impact of the level of knowledge and religiosity on one's intention or intention to buy halal cosmetic products. This study uses a survey method with an instrument in the form of a questionnaire. The questionnaire will be distributed to various regions throughout Indonesia. Respondents in this study were women in the age range of 18-25 years with consideration of having an understanding and being able to buy cosmetic products. This research was previously tested for validity and reliability. The results of the study stated that knowledge is an important factor in one's intention in purchasing halal cosmetic products. while, the influence of religiosity is positive but not significant which means there is no influence which means that a person has a high or low level of religiousness on his desire to buy halal cosmetic products.